2015
DOI: 10.1039/c5ra01586c
|View full text |Cite
|
Sign up to set email alerts
|

The band gap modulation of monolayer Ti2CO2 by strain

Abstract: Monolayer Ti2CO2: indirect–direct band gap transition under biaxial strain of ∼4% and uniaxial strain of ∼6%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
54
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(60 citation statements)
references
References 18 publications
6
54
0
Order By: Relevance
“…properties including electronic [23,[69][70][71][72][73] , magnetic [61,74] , dielectric [75] and optical properties [76] of MXene have been investigated by computations, subsequently, lots of experiments also focused on these properties to confirm the theoretical predictions. The electronic properties will be summarized here.…”
Section: Electronic Propertiesmentioning
confidence: 98%
“…properties including electronic [23,[69][70][71][72][73] , magnetic [61,74] , dielectric [75] and optical properties [76] of MXene have been investigated by computations, subsequently, lots of experiments also focused on these properties to confirm the theoretical predictions. The electronic properties will be summarized here.…”
Section: Electronic Propertiesmentioning
confidence: 98%
“…It has been found that as the electronegativity difference between the functional groups and the transition metal becomes larger, there is a higher chance for semiconducting MXenes [68]. It should also be noted that semiconducting MXenes can be engineered using strain [69], electric field [70], or by being placed on the other 2D systems [71].…”
Section: Electronic Structuresmentioning
confidence: 99%
“…4 shows the projected density of states and projected band structures for Ti 2 C, Ti 2 CF 2 , and Ti 2 CO 2 . It has also been shown that the band gap of Ti 2 CO 2 and Sc 2 CO 2 can be significantly varied by applying either strain [117,118] or external electric field [119,120].…”
Section: Topologically Trivial Metals and Semiconductorsmentioning
confidence: 99%